2007
DOI: 10.1007/s00431-007-0423-1
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous left coronary artery from pulmonary artery (ALCAPA) in infants: a 5-year review in a defined birth cohort

Abstract: Anomalous left coronary artery from pulmonary artery (ALCAPA) is a rare congenital cardiac malformation. It presents predominantly in infancy with features of myocardial ischaemia or cardiac failure and may be mistaken for common paediatric conditions such as colic, reflux or bronchiolitis. With early surgical correction the prognosis is good, but awareness of this condition is essential for prompt diagnosis and referral to a tertiary cardiac centre. In this report we review the five cases that presented durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
29
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 12 publications
0
29
0
1
Order By: Relevance
“…Previously the incidence was reported to be 1/300000. Brotherton et al (12) reported this figure as 1/4243 in their study they performed in live newborns.…”
Section: Discussionmentioning
confidence: 84%
“…Previously the incidence was reported to be 1/300000. Brotherton et al (12) reported this figure as 1/4243 in their study they performed in live newborns.…”
Section: Discussionmentioning
confidence: 84%
“…This is known as myocardial steal or coronary steal. 12,13 In the infants, the chief symptom was irritability elicited by only slight effort, such as feeding, with signs of poor peripheral perfusion. These features started within 2 months of birth, coinciding with substantial reduction in pulmonary vascular resistance that resulted in coronary steal from the anterolateral aspect of the LV.…”
Section: Discussionmentioning
confidence: 99%
“…19 An embryological defect during foetal cardiac development results in the left coronary artery arising from the pulmonary artery instead of the aorta. 20 This defect may result from either abnormal septation of the conotruncus into the aorta and pulmonary artery or from persistence of the aortic buds that eventually form the coronary arteries. This anomaly is usually isolated, but has occasionally been associated with other congenital heart defects such as patent ductus arteriosus, ventricular septal defect, Tetralogy of Fallot or coarctation of aorta.…”
Section: Discussionmentioning
confidence: 99%